Chiari I Malformation in the Adult. Issue 3 (August 2016) - Everson, Richard G.; Holly, Langston T.; Batzdorf, Ulrich
Abstract : Chiari malformation is a designation for a group of alterations in the posterior fossa architecture having the effect of reducing posterior fossa volume, causing descent of the cerebellar tonsils and occasionally the hindbrain as well as an associated disturbance of normal cerebrospinal fluid (CSF) flow in the area of the foramen magnum. Syringomyelia is often associated with these changes. Although numerous studies have failed to correlate the degree of hindbrain descent with symptom severity and type, newer imaging methods are revealing that disproportion between the volume of the posterior fossa and its contents may lead to alterations in CSF flow dynamics that are ultimately responsible for the clinical symptoms. The optimal surgical management of Chiari malformation is still evolving. Treatment today consists of suboccipital decompression to reestablish optimal CSF flow from the fourth ventricle, recreate a subtonsillar cistern, and relieve brainstem compression.